Country Partnership Framework for the Republic of Honduras for the Period FY16 - FY20 - World Bank Group (World Bank, Washington, DC, 2016)
Honduras’ recent economic performance has been positive, especially taking into account the global economic context. Real Gross Domestic Product (GDP) growth accelerated from 2.8 percent in 2013 to 3.1 percent in 2014 and 3.6 percent in the first half of 2015. Growth has been supported by improved terms of trade, higher remittance inflows and export demand driven by the on-going recovery of the United States (US), and improved investor confidence. The new Country Partnership Framework (CPF) seeks to support Honduras in its efforts to foster social inclusion, while bolstering conditions for growth and reducing vulnerabilities to enhance the country’s resilience. The Government’s 2014-2018 Plan for a Better Life focuses on four areas: (i) fostering peace and reducing violence; (ii) generating employment and enhancing competitiveness; (iii) reducing inequality and improving social protection for enhanced human development; and (iv) enhancing transparency and modernization of the State. The CPF seeks to support critical components of this Plan, with an emphasis on the themes of social inclusion, growth and resilience, also highlighted as priorities in the WBG’s SCD.